2020 Crisis Preparedness Exercise with EFSA Focal Points & Observers. Issue 11 (13th November 2020) - Johnson, Julia; Upton, Jen; Vincent, Andrew; ,; Gkrintzali, Georgia; ,
Abstract : In September 2020, the European Food Safety Authority (EFSA) facilitated an online workshop on crisis preparedness and procedures with Members and Observers of EFSA's Focal Point Network. The overall aims of the event were, in the context of a food or feed safety incident, (i) to establish the most appropriate ways to improve collaboration—and exchange data & information—between EFSA and Focal Points, in EU Member States and Pre‐Accession Countries; (ii) identify gaps and frustrations in the current system and look for ways to improve; and (iii) share best practice and knowledge to improve ways of working. Content for the workshop was jointly developed between EFSA and Instinctif Partners. Sixty‐three (63) participants attended plenary and/or working group activity sessions configured within an agenda extending across two days.During Day One, four plenary activities (including presentations and structured discussions) aimed to clarify the role played by Focal Point Network members during incident response, plus the frustrations and challenges arising from fulfilling that role. A working group activity focused on finding solutions and workarounds to the problems and challenges identified. The Day One afternoon session was a two‐hour discussion exercise designed to elaborate the real‐world incident response activities potentially undertaken by Focal Points in the case of a fast‐evolving, large‐scale foodborne disease outbreak. The fictional scenario for the exercise was based on a hypothetical situation where a novel pathogenic virus (similar to SARS‐CoV‐2) turned out to be transmissible in certain food products. Day Two of the event included a 1.5‐hour facilitated plenary debrief of the Day One discussion exercise. The objectives of the event were achieved, based on the recorded outcomes and feedback provided by participants in an online evaluation survey. In addition, discussions during the event generated eighteen (18) practical recommendations for future enhancements and improvements.